TRANSVERSE ENERGY-DISTRIBUTIONS WITHIN JETS IN P(P)OVER-BAR COLLISIONS AT ROOT-S=1.8 TEV - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Alvarez, G; Alves, G; et al. (1995)
The distribution of the transverse energy in jets has been measured in pp collisions at s=1.8 TeV TeV using the DØ detector at Fermilab. This measurement of the jet shape is made as a function of jet transverse energy in both the central and forward rapidity regions. Jets are shown to narrow both with increasing transverse energy and with increasing rapidity. Next-to-leading order partonic QCD calculations are compared to the data. Although the calculations qualitatively describe the data, they are shown to be very dependent on renormalization scale, parton clustering algorithm, and jet direction definition and they fail to describe the data in all regions consistently. © 1995.